Blue, green, and orange-red emission from Polystyrene microbeads for solid-state white-light and multicolor emission - Sonawane, Swapnil L.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
Solid-state white-light emission was achieved from polystyrene (PS) microbeads incorporated with fluorophores based on perylene bisimide (PBITEG) and oligo(p-phenylenevinylene) (OPV) as acrylic cross-linkers. The PS beads incorporated with only PBITEG gave intense orange-red emission; PS incorporated with OPV exhibited blue-emission, whereas a series of polymers incorporating both cross-linkers exhibited varying shades of white-light emission. One of the PS samples, PS-PBITEG-6.25-OPV-4.28 (PBITEG incorporation: 6.25 X 10(-7) mole; OPV incorporation: 4.28 x 10(-7) mol), exhibited pure white-light emission in the powder form with CIE coordinates (0.33, 0.32). The rigid aromatic cross-linkers were incorporated into the PS backbone in a two-stage dispersion polymerization to afford PS beads in the size range 2 to 3 mu m. The incorporation of fluorophores as cross-linkers enabled covalent attachment of the dye to the polymer backbone, avoiding dye leakage besides avoiding aggregation-induced fluorescence quenching.

Biodegradable, solvent-free photocrosslinkable PLLA resin formulations for additive manufacturing - Pal, Shibam; Asha, S. K. (Macromolecular Chemistry and Physics, 2022)
Acrylate end-functionalized linear and star poly l-lactide (PLLA) based aliphatic, photocurable oligomeric crosslinkers are developed, which are formulated with hydroxyl (ethyl)methacrylate (HEMA) as a biodegradable reactive diluent to demonstrate successful application for solvent-less 3D printing using digital light processing (DLP) technique as well as a custom-designed direct ink writing 3D printer. The resin formulation for 3D printing is optimized using spot curing, photodifferential scanning calorimetry and cure depth analysis. The 3D printed parts exhibit promising mechanical property along with improved hydrophilicity and biodegradability. The development of new photocurable resin formulations are expected to meet the growing demand for raw materials that can be applied for developing custom designed bio implantable objects.
Keywords: 3D printing; biodegradable materials; digital light processing; L-Lactide; photocurable materials

Biocompatible PVAc-g--PLLA acrylate polymers for DLP 3D printing with tunable mechanical properties - Pal, Shibam; Gavhane, Utreshwar Arjun; Asha, S. K. (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: acid; copolymers; polymerization; TACONIC ANHYDRIDE